MAPPING THE NEXUS OF GREEN MARKETING, RELIGIOSITY, AND CONSUMER BEHAVIOR: A SYSTEMATIC LITERATURE REVIEW - Lili Fadli Muhamad; Mohd Zulkeflee Bin Abd Razak (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2025)
The increasingly dire state of the environment worldwide has made sustainable consumption a major focus, placing green marketing in the forefront as an important corporate strategy. Similarly, the role that religiosity, especially in Muslim consumer settings, plays concerning purchase intention has gained considerable attention. This systematic literature review aggregates findings from 50 recent scholarly articles that examine interlinkages between green marketing strategies, religious values, and consumers' decision-making processes. The review revealed that although green marketing significantly leads to consumer behavioral change, perceived authenticity, transparency, and reduction of green washing often act as moderators that impede or enhance its performance. Besides, religiosity was proven to be one of the strong predictors of green purchase intention, and studies have emphasized its role in setting ethical consumption patterns among Muslim consumers. The review summarized that the Theory of Planned Behavior was the most used theoretical framework, and there is an increasing trend in bibliometric and systematic review approaches. The main challenges for green marketing strategies include consumer skepticism and high prices of green products, while digital transformation and social media were identified as key enablers for future green marketing strategies. The study offers an integrated framework for this multidisciplinary area and suggests some actionable insights for academia and practitioners.